2008
DOI: 10.1111/j.1365-2648.2008.04660.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an online course on infection control and prevention competencies

Abstract: Online learning can provide ongoing, convenient and effective access to up-to-date information on best practices in infection control and prevention. This standardized delivery approach minimizes demand on limited training resources which are under strain and gives learners the opportunity to refresh 'rusty' infection control and prevention skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 6 publications
2
27
0
1
Order By: Relevance
“…A study that examined the impact of an online course on healthcare professionals’ competency in infection prevention using questionnaires applied before and after the course for knowledge evaluation, concluded that the participants made statistically significant increases in their perceptions of competency in infection control following the course. Additionally, most of the participants were very pleased and reported that the acquired knowledge was useful and relevant for their professional practice 1 .…”
Section: Resultsmentioning
confidence: 98%
“…A study that examined the impact of an online course on healthcare professionals’ competency in infection prevention using questionnaires applied before and after the course for knowledge evaluation, concluded that the participants made statistically significant increases in their perceptions of competency in infection control following the course. Additionally, most of the participants were very pleased and reported that the acquired knowledge was useful and relevant for their professional practice 1 .…”
Section: Resultsmentioning
confidence: 98%
“…This last point is perhaps the most important, for in order for education to be effective, it must result in the effective translation into practice of the skills learned online. 1,2 This article outlines the design philosophy of the Institute and provides models for best practice development in online IPE.…”
Section: Introductionmentioning
confidence: 99%
“…All reported scores were adjusted. As in previous studies, a score of 13/20 (65%) was considered satisfactory (14).…”
Section: Methodsmentioning
confidence: 85%